2021
DOI: 10.32598/rj.22.3.3259.1
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of Accessing and Using Rehabilitation Services in People With Autism Spectrum Disorder: A Systematic Review

Abstract: Objective: One of the essential needs of patients with Autism Spectrum Disorder (ASD) and their families is the rehabilitation services to improve patients’ performance in social interactions and communication. However, access and use of these services pose many challenges for patients with ASD and service providers. This study systematically reviews the challenges of access and use of rehabilitation services for patients with ASD. Materials & Methods: This is a systematic review of the articles published … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Previous research findings underscore that the deficiency in health insurance coverage has been linked to inadequate access to rehabilitation services, resulting in prolonged appointment delays for PWDs in Iran. This highlights the need for increased attention and policy consideration in addressing the gaps in coverage for these essential services ( 13 , 30 - 32 ). Given that long-term therapies can impose significant financial burdens on PWDs and their families, it becomes imperative to implement health policy reforms in Iran.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research findings underscore that the deficiency in health insurance coverage has been linked to inadequate access to rehabilitation services, resulting in prolonged appointment delays for PWDs in Iran. This highlights the need for increased attention and policy consideration in addressing the gaps in coverage for these essential services ( 13 , 30 - 32 ). Given that long-term therapies can impose significant financial burdens on PWDs and their families, it becomes imperative to implement health policy reforms in Iran.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Vameghi et al [ 28 ] in Iran indicated that lack of awareness in families was a key factor for delay in access to Speech and language therapy services. Similarly, Aarabi et al [ 29 ] in a systematic review found that lack of information about needed services among parents was a major barrier to access to rehabilitation services among people with spectrum disorders in Iran.…”
Section: Discussionmentioning
confidence: 99%